2017
DOI: 10.1530/eje-17-0145
|View full text |Cite
|
Sign up to set email alerts
|

Altered sleep patterns in patients with non-functional GHRH receptor

Abstract: Patients with IGHD due to GHRH resistance exhibit objective reduction in the sleep quality, with changes in NREM and REM sleep, with no detectable subjective consequences. GHRH resistance seems to have a preponderant role over GHD in the sleep quality of these subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…IGHD individuals exhibit normal quality of life ( 27 ), despite shorter and more fragmented sleep ( 53 ). The external and internal genitalia are essentially normal, which guarantees sexual life with a person of normal stature, with preserved reproductive capacity ( 20 , 24 , 25 , 54 ).…”
Section: Body Functions In Itabaianinha Syndromementioning
confidence: 99%
“…IGHD individuals exhibit normal quality of life ( 27 ), despite shorter and more fragmented sleep ( 53 ). The external and internal genitalia are essentially normal, which guarantees sexual life with a person of normal stature, with preserved reproductive capacity ( 20 , 24 , 25 , 54 ).…”
Section: Body Functions In Itabaianinha Syndromementioning
confidence: 99%
“…In addition, one subject who had GH replacement therapy earlier in her life, developed an ependymoma and appears to be tumor-free after surgical treatment. It was also shown that subjects with this syndrome have a reduction in sleep quality with no subjective consequences on the quality of life [ 67 ], deeper periodontal pockets with locally increased levels of several immune mediators [ 68 ], as well as higher prevalence of modest vestibular impairment and abnormal vestibular ocular reflex, likely related to the reported dizziness but without negative effects on postural balance or fall risk [ 69 ]. Furthermore, IGHD subjects had improved insulin sensitivity (ower homeostatic model assessment for insulin resistance [HOMA-IR], reduced creatine phosphokinase [CPK], higher C-reactive protein [CRP], lower sweating, normal vitamin D levels, and normal phosphorus: calcium homeostasis [ 70 ].…”
Section: Novel Findings In Individuals With Growth Hormone Deficiency or Growth Hormone Resistancementioning
confidence: 99%
“…Factors that affect thyroid function during pregnancy include iodine [ 3 ], human chorionic gonadotropin (hCG) concentration [ 4 ], the placenta [ 5 ], body mass index [ 6 ], and ethnicity [ 7 ]. As thyroid physiology changes during pregnancy due to these factors, each trimester should have its own TSH reference range based on the population of pregnant women.…”
mentioning
confidence: 99%